Modeling of gas–liquid flow in a rotating packed bed using an Eulerian multi‐fluid approach. Issue 4 (10th January 2022) - Zhang, Wei; Xie, Peng; Li, Yuxing; Zhu, Jianlu
Abstract: Rotating packed beds (RPBs) are ideal candidates for CO2 removal from offshore natural gas due to their good mass transfer performance and significant volume savings. This article proposes an Eulerian multi‐fluid approach to simulate the gas–liquid flow in RPBs. Three new multiphase drag force models are constructed based on single‐phase drag force models for wire mesh packings. Based on the Eulerian multi‐fluid approach, a new RPB simulation framework is developed. The predicted results using the new simulation framework with the new drag force models are compared with the experimental data. When using the Kołodziej model and the modified Kołodziej model, the predicted overall liquid holdup shows good agreement with the experimental data with errors less than 20%. In addition, the pressure drop predicted by these three models are reasonable compared with the experimental data. This work lays a foundation for RPB simulation of gas–liquid flow using Eulerian multi‐fluid approach.